Efecto de diferentes porcentajes de harina de tilapia en parámetros productivos e incidencia de escherichia coli en pollos. - Flores Salazar, Daniela Fernanda (2025)
Poultry production has grown worldwide, especially in Ecuador, where chicken meat is a key source of protein. Nutrient-rich tilapia meal is presented as an alternative to reduce production costs. However, its inclusion could increase the presence of Escherichia coli in poultry, which could pose a risk to human health. The objectives were: 1) To determine the optimal percentage of tilapia meal for chicken production parameters. 2) To determine the presence of Escherichia coli in chickens. 3) To perform an economic analysis of the benefit/cost ratio. The research was conducted in the San Simón parish, Guaranda canton, using a Randomized Complete Block Design (RCBD) with four replications. The results showed that the inclusion of gray tilapia meal in the chicken diet significantly improved production parameters, achieving the highest final weight of 2899.94 g and the highest weight gain of 636.02 g/chicken at week 6, with a more efficient feed conversion ratio of 1.81. Regarding the presence of E. coli, the treatment with 2% tilapia meal showed the lowest levels of the bacteria in feces, at 3.10 × 10⁶ CFU/g, and in intestines, at 6.80 × 10³ CFU/g, indicating better intestinal health. The economic analysis showed that the treatment with 3% tilapia meal was the most profitable, with a benefit/cost ratio of 1.23.